Antimicrobial, Antivirulence, and Antiparasitic Potential of Capsicum chinense Jacq. Extracts and Their Isolated Compound Capsaicin - Ralciane de Paula Menezes; Meliza Arantes de Souza Bessa; Camila de Paula Siqueira; Samuel Cota Teixeira; Eloisa Amália Vieira Ferro; Mário Machado Martins; Luis Carlos Scalon Cunha; Carlos Henrique Gomes Martins (MDPI AG, 2022)
Bacterial, fungal, and parasitic infections increase morbimortality rates and hospital costs. This study aimed to assess the antimicrobial and antiparasitic activities of the crude extract from the seeds and peel of the pepper Capsicum chinense Jacq. and of the isolated compound capsaicin and to evaluate their ability to inhibit biofilm formation, eradicate biofilm, and reduce hemolysin production by Candida species. The crude ethanolic and hexane extracts were obtained by maceration at room temperature, and their chemical compositions were analyzed by liquid chromatography coupled to mass spectrometry (LC-MS). The antimicrobial activity of the samples was evaluated by determining the minimum inhibitory concentration. Inhibition of biofilm formation and biofilm eradication by the samples were evaluated based on biomass and cell viability. Reduction of Candida spp. hemolytic activity by the samples was determined on sheep blood agar plates. The antiparasitic action of the samples was evaluated by determining their ability to inhibit Toxoplasma gondii intracellular proliferation. LC-MS-ESI analyses helped to identify organic and phenolic acids, flavonoids, capsaicinoids, and fatty acids in the ethanolic extracts, as well as capsaicinoids and fatty acids in the hexane extracts. Antifungal action was more evident against C. glabrata and C. tropicalis. The samples inhibited biofilm formation and eradicated the biofilm formed by C. tropicalis more effectively. Sub-inhibitory concentrations of the samples significantly reduced the C. glabrata and C. tropicalis hemolytic activity. The samples only altered host cell viability when tested at higher concentrations; however, at non-toxic concentrations, they reduced T. gondii growth. In association with gold standard drugs used to treat toxoplasmosis, capsaicin improved their antiparasitic activity. These results are unprecedented and encouraging, indicating the Capsicum chinense Jacq. peel and seed extracts and capsaicin display antifungal and antiparasitic activities.